LEGAL PROTECTION OF FAMOUS TRADEMARKS - Iqbal, Mohammad; Nugroho, Erdyanto Dwi (Universitas Semarang, 2021)
The purpose of this study is to analyze the legal protection of well-known brands. The use of well-known brands at this time has begun to flourish, this is because it promises great benefits to be obtained when using well-known brands rather than using their own brands. Many manufacturers have got around to combining original branded goods with pirated ones, because the pirated is physically similar to the original. In this articlethat what determines a brand is the community because it is the public who knows that a brand is worthy of being famous. So, one way is through Preventive and Repressive Protection in accordance with Law 20 of 2016, there is a need for amendments toa definite measure for the Judge to determine the criteria for a famous mark and also provide criteria that can distinguish the similarity in essence from the overall equation and the philosophical requirements of a brand.